Search for potential hypoglycemic agents among potassium salts of 3-benzyl-8-substituted xanthines - Aleksandrova, K. V.; Pruhlo, Ye. S.; Mykhalchenko, Ye. K.; Shkoda, O. S.; Cherchesova, O. Yu.; Александрова, Катерина Вячеславівна; Пругло, Євген Сергійович; Михальченко, Євген Костянтинович; Шкода, Олександр Станіславович; Черчесова, Олександра Юріївна (Запорізький державний медичний університет, 2022)
The aim of the study was to explore the hypoglycemic activity of newly synthesized water-soluble derivatives of 3-benzyl-8-substituted xanthines. Materials and methods. We obtained water-soluble potassium 3-benzyl-8-R-xanthin-7-ides, the structure and individuality of which were confirmed by a set of physical-chemical studies. Results. The hypoglycemic effect of the newly synthesized compounds was assessed by an oral glucose tolerance test. The obtained data were processed using modern statistical in silico-methods. Conclusions. The results of the hypoglycemic activity study among the potassium salts of 3-benzyl-8-substituted xanthine derivatives showed, that some new compounds are in close vicinity to the reference drug’s hypoglycemic action. Мета роботи – дослідження гіпоглікемічної активності новосинтезованих водорозчинних похідних 3-бензил-8-заміщених ксантинів. Матеріали та методи. Одержали водорозчинні калій 3-бензил-8-R-ксантиніди-7, будову та індивідуальність яких підтверджено комплексом фізико-хімічних досліджень. Результати. Гіпоглікемічну дію новосинтезованих сполук оцінили за допомогою перорального тесту толерантності до глюкози. Результати опрацювали за допомогою сучасних статистичних in silico-методів. Висновки. Результати дослідження гіпоглікемічної активності серед новосинтезованих калієвих солей 3-бензил-8-заміщених ксантинів підтверджують наявність сполук, що за рівнем гіпоглікемічної дії наближаються до референс-препарату.
Пошук потенційних гіпоглікемічних засобів серед калієвих солей 3-бензил-8-заміщених ксантинів
Aleksandrova K. V. - ORCID ID: 0000-0003-4436-4036; Pruhlo Ye. S. - ORCID ID: 0000-0002-4705-7261; Mykhalchenko Ye. K. - ORCID ID: 0000-0002-6388-2966; Shkoda O. S. - ORCID ID: 0000-0002-5678-2801; Cherchesova O. Yu. - ORCID ID: 0000-0001-9798-7128.
Keywords: xanthines; organic synthesis; hypoglycemic activity; ксантини; органічний синтез; гіпоглікемічна активність